An analysis of the effects of environmental factors on conidial dispersal of uncinula necator (grape powdery mildew) in vineyards - Willocquet, L.; Clerjeau, M. (Wiley, 1998)
Aerial spore concentration of Uncinula necator (the causal agent of grape powdery mildew), weather data and cropping practices were monitored during two consecutive seasons in two vineyards of the Bordeaux area. During days with no rain, spore dispersal was mainly diurnal and showed variations that followed the same pattern as that of wind speed, and a reverse pattern to that of relative humidity. Light falls of rain, of approximately 2 mm, coincided with increased spore densities in the air. Pesticide sprays using high pressure equipment generated high wind speeds at the canopy level. This may trigger high spore dispersal. High conidial stocks were produced under spontaneous conditions in the canopy. These stocks were released only under particular events, such as heavy rains, or pesticide applications with high pressure sprayers. Other cropping practices causing leaf shaking, such as pruning, may enhance spore dispersal. Over the observation period, the onset of spore dispersal was observed during a period with no rain following a rainy period, suggesting the detrimental effect of rains on epidemic onset. Epidemiological and disease management implications are discussed.